2002
DOI: 10.1021/jo025813f
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of (+)-Boronolide

Abstract: The delta-lactone boronolide (+)-1, a pharmacologically active, naturally occurring product, has been synthesized in enantiopure form with L-erythrulose as the chiral starting material. The key steps of the synthesis were a highly stereoselective aldol-reduction one-pot sequence, an indium-mediated diastereoselective aldehyde allylation, and a ring-closing metathesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It appeared that we required a protecting group on the side‐chain that could be removed under conditions that would circumvent cyclisation onto the C‐5 ketone. We therefore selected acetonide‐protected iodide 20 as our alternative side‐chain fragment, as oxidative cleavage of the acetonide33 would afford aldehyde 18 directly (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appeared that we required a protecting group on the side‐chain that could be removed under conditions that would circumvent cyclisation onto the C‐5 ketone. We therefore selected acetonide‐protected iodide 20 as our alternative side‐chain fragment, as oxidative cleavage of the acetonide33 would afford aldehyde 18 directly (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation of alcohol 22 to the ketone with IBX in DMSO gave hexahydroindanedione 23 in high yield. The acetonide was transformed into aldehyde 18 by deprotection/oxidative cleavage using periodic acid in ethyl acetate in moderate yield 33. The final step to complete the synthesis of DOHNAA was a Pinnick oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…5,7 In the case of 5, a similar analysis leads to 2,6-dideoxy-L-xylohexose (L-boivinose), a monosaccharide which is not available commercially (Scheme 1). Several syntheses of this and related 2,6-dideoxyhexoses have been previously reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…bulkier R 1 -group occupies the outer position of the ring antiperiplanar to the bond being formed, while the α-Me group is oriented away from the metal, to explain the observed selectivity [27]. The robustness of this chemistry can be seen in the total synthesis of zincophorin (46) by Cossy and coworkers [28] and studies toward the total synthesis of saliniketal A (50) by L.C. Dias and C.C.…”
Section: 4-asymmetric Induction Using α-Methyl-β-branched Ketonesmentioning
confidence: 97%
“…This chemistry was applied in the total synthesis of (+)-boronolide (103) [46]. In these studies, the authors observed that addition of the boron enolate generated from methyl ketone 104 to aldehyde 105 produced aldol adduct 106, which has a 1,5-anti relationship between the β-alkoxy group and the newly formed stereogenic center.…”
Section: 4-asymmetric Induction Using α-Alkoxy Ketonesmentioning
confidence: 99%